State of young stands regenerated with oak, alder or larch in Finland - Männistö, Lauri; Miettinen, Janne; Miina, Jari; Huuskonen, Saija; Paananen, Raito; Luoto, Minna; Himanen, Katri (Taylor & Francis, 2026)
Climate change and the appreciation of biodiversity have sparked an increasing interest to widen the traditionally limited tree species composition of Nordic silviculture. It has been recognized that Black alder, Siberian larch, and English oak might have enough economic potential to be a viable alternative to commonly utilized conifers on some sites. The aim of this study is to examine the current state of young stands regenerated with these selected tree species in Finland and to pinpoint current silvicultural shortcomings, which hinder the forestry of these species. Inventories of 46 sapling stands were carried out and their silvicultural state was assessed. We discovered that even though stands rarely met the standards of silvicultural recommendations, intended main tree species were rarely suppressed by naturally emerged saplings, and serious damage was not common. Sites regenerated with these less utilized tree species were generally suitable for the chosen species. Increasing the proportion of oak, alder and larch seems to be a viable option for diversifying the tree species composition. More precise silvicultural recommendations are needed, and they need to be adopted in practice, as most issues found were related to the quality of forest management.
Keywords: juvenile stand management; species diversity; Black alder; larch; oak